Perbandingan Yield Material dan Standard Kerja TSKK - Dodgalih Nur Muhammad; Jani Rahardjo (Jurnal Titra, 2017)
This study was done to make a method in Yield material factor collection system, to know the cause of deviation of production output with Yield material, to know Yield standard still relevant or not and to search first data of production activity at press manufacturing area. First problem is workers are not writing down on worker daily report the actual output of production. Second problem is to know the cause of deviation of production output with Yield material. Third probelm is to know wether Yield standard used to relevant with current condition or not. Last problem is workers do unnecessary activity in production proses. Improvement for first problem is making a new method using work instruction. Improvement for second problem is using fishbone diagram to know the root cause of the problem. Third problem is searching actual Yield, if actual Yield different with standard Yield then make a new Yield standard for each type of component. Last problem is only taking the first data in the form of SWCS and the suggestion is to make a new work instruction contains activities which workers have to do and a warning if workers are not doing activities as written on work instruction.